Curcumin preconditioning enhances the efficacy of adipose-derived mesenchymal stem cells to accelerate healing of burn wounds. Issue 1 (11th September 2021) - Azam, Maryam; Ghufran, Hafiz; Butt, Hira; Mehmood, Azra; Ashfaq, Ramla; Ilyas, Asad M; Ahmad, Muhammad R; Riazuddin, Sheikh
Abstract: Background: Following recent findings from our group that curcumin preconditioning augments the therapeutic efficacy of adipose-derived stem cells in the healing of diabetic wounds in rats, we aimed to investigate the regenerative effects of curcumin preconditioned adipose-derived mesenchymal stem cells (ASCs) for better recovery of acid inflicted burns in this study. Methods: ASCs were preconditioned with 5 μM curcumin for 24 hours and assessed for proliferation, migration, paracrine release potential and gene expression comparative to naïve ASCs. Subsequently, the healing capacity of curcumin preconditioned ASCs (Cur-ASCs) versus naïve ASCs was examined using acidic wounds in rats. For this, acid inflicted burns of 20 mm in diameter were made on the back of male Wistar rats. Then, 2 × 10 6 cells of Cur-ASCs and naïve ASCs were intradermally injected in the wound periphery (n = 6) for comparison with an untreated saline control. Post-transplantation, wounds were macroscopically analysed and photographed to evaluate the percentage of wound closure and period of re-epithelization. Healed wound biopsies were excised and used for histological evaluation and expression analysis of wound healing markers at molecular level by quantitative PCR and western blotting. Results: We found that Cur-ASCs exhibited greater proliferation, migration and paracrine potential in vitro . Further, Cur-ASCs showed more effective recovery than naïve ASCs as exhibited by gross morphology, faster wound closure and earlier re-epithelialization. Masson's trichrome and hematoxylin and eosin staining demonstrated the improved architecture of the healing burns, as evidenced by reduced infiltration of inflammatory cells, compact collagen and marked granulation in Cur-ASC treated rats. Corroborating these findings, molecular assessment showed significantly reduced expressions of pro-inflammatory factors (interleukin-1 beta, interleukin-6, tumor necrosis factor alpha) a with striking upsurge of an oxidative marker (superoxide dismutase 1), pro-angiogenic factors (vascular endothelial growth factor, hepatocyte growth factor, hypoxia-inducible factor-1 alpha) and collagen markers (transforming growth factor beta 1, fibroblast growth factor-2, collagen type 1 alpha 1), verifying that Cur-ASCs modulate the regulation of pro-inflammatory and healing markers at burn sites. Conclusions: Treatment with Cur-ASCs resulted in faster re-epithelization of acid inflicted burns compared to the treatment with naïve ASCs. Based on observed findings, we suggest the transplantation of Cur-ASCs is a valuable therapy for the potent clinical management of acidic burns.